Expressive and interactive potentialities online :|discussion and the reproduction of “Good Motherhood” on instagram - Şentürk, Ekin Yağan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis aims at analyzing the expressive and communicative potentialities that Social Networking Services (SNSs) provide for mothers. Occupying an important position in our daily lives, the SNSs gradually enabled individuals to connect whereas the transformations of urbanization and individualization altered the existing ways for interaction, communication, and knowledge production. The findings of this thesis suggest that mothers’ online interactivity enables more open and “honest” expressions about experiences of motherhood, on topics that cannot be openly expressed in their social networks. With its fleeting and speedy nature, Instagram seems to be a digital tool from which mothers can receive emotional validation and support. Moreover, as this thesis will emphasize, Instagram also operates as a tool through which mothers criticize, discuss and resist the particular ideals of “good motherhood.” This thesis will further elaborate how the shared struggles give way to a sense of “commonality.” In order to provide a balanced analysis, this thesis will also discuss how these “common” problems are often not contextualized and how discourses over mother love, and how using humor are utilized as tools for overcoming these structural problems individually.
Keywords: Motherhood.; Instagram (Firm); Digital media.; Online social networks.